Multiscale skin imaging in vivo using optical coherence tomography. (17th May 2018) - Yu, Xiaojun; Tang, Hongying; Hu, Chi; Ding, Qianshan; Wang, Lulu; Wang, Xianghong; Fan, Zeming; Liu, Linbo
Abstract: Optical coherence tomography (OCT) is a noninvasive high-resolution diagnostic imaging modality that plays an increasingly important role in dermatology. Diagnosis of skin diseases using OCT requires both cellular-level high resolution and large area skin coverage. In practice, however, there exists a trade-off between the achievable spatial resolutions and the transverse scanning range. In this study, we report a Micro-OCT ( μ OCT) system that is capable of providing three-dimensional images of the skin at multiple spatial scales with both cellular-level resolution (1–2 μ m) mode and large area (̃ mm 2 ) scanning mode. Specifically, in the cellular-level scanning mode, we achieve a transverse resolution of ̃1.5 μ m and an axial resolution of 1.7 μ m ( n = 1.38) which enables the visualization of cellular-level skin microstructures. While in the large-area scanning mode, the system is capable of covering an en face imaging area reaching up to with a lateral resolution of ̃5.5 μ m at a scanning speed of 60 K Alines/s. We experimentally verify the imaging capabilities of such a multiscale μ OCT system including in vivo visualization of epidermal cells in the cellular-level scanning mode as well as the internal fingerprints and sweat gland ducts in the large area scanning mode. Micro-anatomical imaging at multiple spatial scales could provide comprehensive information of the skin that is valuable to disease diagnosis.